Keterlibatan Perempuan dan Kebijakan Daerah dalam Pembangunan Responsif Gender di Kabupaten Berau - Winda Jubaidah (ECO-BUILD, 2025)
This study analyzes the issue of gender equality and the role of women in development in Berau Regency, East Kalimantan, with a qualitative descriptive approach based on secondary data. The study found that while women's involvement in development is increasing – including the presence of women leaders in local government – there are a number of gender issues, such as lower female labour force participation, limited representation in strategic positions, and cultural norms that hinder equality. The Berau Regency Government has implemented various gender-responsive policies, including gender mainstreaming (PUG) in regional planning through RPJMD and local regulations (Perda and Perbup), as well as innovative programs such as Women-Friendly Villages and Child Care. Through the analysis of the literature and BPS data, this study recommends strengthening the implementation of PUG, increasing women's participation in the public and economic sectors, and disaggregated data-based monitoring and evaluation frameworks.